Environmental Occurrence, Toxicity Concerns, and Degradation of Diazinon Using a Microbial System - Wu, Xiaozhen; Li, Jiayi; Zhou, Zhe; Lin, Ziqiu; Pang, Shimei; Bhatt, Pankaj; Mishra, Sandhya; Chen, Shaohua (Frontiers in Microbiology, 2021)
Diazinon is an organophosphorus pesticide widely used to control cabbage insects, cotton aphids and underground pests. The continuous application of diazinon in agricultural activities has caused both ecological risk and biological hazards in the environment. Diazinon can be degraded via physical and chemical methods such as photocatalysis, adsorption and advanced oxidation. The microbial degradation of diazinon is found to be more effective than physicochemical methods for its complete clean-up from contaminated soil and water environments. The microbial strains belonging to Ochrobactrum sp., Stenotrophomonas sp., Lactobacillus brevis, Serratia marcescens, Aspergillus niger, Rhodotorula glutinis, and Rhodotorula rubra were found to be very promising for the ecofriendly removal of diazinon. The degradation pathways of diazinon and the fate of several metabolites were investigated. In addition, a variety of diazinon-degrading enzymes, such as hydrolase, acid phosphatase, laccase, cytochrome P450, and flavin monooxygenase were also discovered to play a crucial role in the biodegradation of diazinon. However, many unanswered questions still exist regarding the environmental fate and degradation mechanisms of this pesticide. The catalytic mechanisms responsible for enzymatic degradation remain unexplained, and ecotechnological techniques need to be applied to gain a comprehensive understanding of these issues. Hence, this review article provides in-depth information about the impact and toxicity of diazinon in living systems and discusses the developed ecotechnological remedial methods used for the effective biodegradation of diazinon in a contaminated environment.